Development of attention concentration and stability of railway students in the process of psychological and psychophysical training - Pichurin, V. V. (Science and Transport Progress, 2014)
Purpose. Some railway professions impose exceptionally high demands on such characteristics of railway students as concentration and stability. One should find out the conditions for effective development of these characteristics in the process of physical training. Methodology. Pedagogical experiment is the main method of research. During this experiment the content of psychological and psychophysical training foundations developed by the author was an independent value. A dependent value was the dynamics performance of the level of development of concentration and stability of railway students’ attention. Findings. It was established, that realization of measure complex (included by the author to the content of foundations of psychological and psychophysical training of railway students) during the lessons is the effective direction of the development of the attention concentration and stability. Originality. The effectiveness of using the psychological and psychophysical training of students for development of attention concentration and stability during the lessons was confirmed. Practical value. Realization of the proposed approach during the training of specialists for the railway branch will increase the productivity and safety of railway transportations.